Perception of musical pitch in developmental prosopagnosia. (18th February 2019) - Corrow, Sherryse L.; Stubbs, Jacob L.; Schlaug, Gottfried; Buss, Stephanie; Paquette, Sebastien; Duchaine, Brad; Barton, Jason J.S.
Abstract: Studies of developmental prosopagnosia have often shown that developmental prosopagnosia differentially affects human face processing over non-face object processing. However, little consideration has been given to whether this condition is associated with perceptual or sensorimotor impairments in other modalities. Comorbidities have played a role in theories of other developmental disorders such as dyslexia, but studies of developmental prosopagnosia have often focused on the nature of the visual recognition impairment despite evidence for widespread neural anomalies that might affect other sensorimotor systems. We studied 12 subjects with developmental prosopagnosia with a battery of auditory tests evaluating pitch and rhythm processing as well as voice perception and recognition. Overall, three subjects were impaired in fine pitch discrimination, a prevalence of 25% that is higher than the estimated 4% prevalence of congenital amusia in the general population. This was a selective deficit, as rhythm perception was unaffected in all 12 subjects. Furthermore, two of the three prosopagnosic subjects who were impaired in pitch discrimination had intact voice perception and recognition, while two of the remaining nine subjects had impaired voice recognition but intact pitch perception. These results indicate that, in some subjects with developmental prosopagnosia, the face recognition deficit is not an isolated impairment but is associated with deficits in other domains, such as auditory perception. These deficits may form part of a broader syndrome which could be due to distributed microstructural anomalies in various brain networks, possibly with a common theme of right hemispheric predominance. Highlights: Some prosopagnosic subjects showed deficits in pitch processing relative to controls. Individually, 25% of the prosopagnosia sample scored in the tone deaf range. These subjects were impaired in pitch processing, but not rhythm. Face recognition ability significantly predicted pitch processing ability.